Get ready to Duck. Bouncers and the realities of ethnographic research on violent groups - Winlow, Simon; Hobbs, Dick; Lister, Stuart; Hadfield, Philip (The British journal of criminology, 2001)
This paper seeks to address some of the pragmatic and ethical issues encountered when researching violence. We seek through reference to our own work and to the work of others to highlight the inevitability of these problems and to suggest that dealing with them is instrinsic to the sociological enterprise